Short synthetic oligodeoxyribonucleotide leader sequences enhance accumulation of human proinsulin synthesized in Escherichia coli. - Sung, W L (1986)
Enhanced accumulation of human proinsulin synthesized in Escherichia coli has been achieved by inserting a short leader of homooligopeptide at the amino end of proinsulin. Out of 20 amino acid oligomers studied, (Ala)6, (Asn)6, (Cys)7, (Gln)7, (His)6, (Ser)6, and (Thr)6 leaders were the most effective, with the yield of proinsulin ranging between 6% and 26% of the total bacterial protein. These constructions were made by inserting a synthetic oligodeoxyribonucleotide duplex, coding for a small homooligopeptide, between a synthetic proinsulin gene and an eight-codon beta-galactosidase gene residue in vector pUC8. Cyanogen bromide cleavage of the 102 amino acid fused polypeptide yielded a species identical to authentic proinsulin, as judged by NaDodSO4/PAGE and radioimmunoassay.